Acoustic Vowel Analysis of Costa Rican Children - Coto Jiménez, Marvin (2020)
This paper presents an acoustic analysis of vowels pronounced by a group of Costa Rican children, aged between six and twelve years. These analyses aim to achieve a better understanding of the speech characteristics produced by this particular group and thus provide important information for the improvement of automatic speech recognizers and speaker identification. For this purpose, a database consisting of isolated words was built, which contains the phonemes according to various stages of language development in children. Additionally, a strategy for interaction with them was developed. The results confirm and complement the results reported in the literature, showing that a greater variability of speech parameters such as formants, tone, and duration are present in children in comparison to adults. The results allow the characterization of these speech sounds and the possibility of establishing future research in areas such as speech recognition and its dependence on gender and age in this community.